P074: Improving urology care in the emergency department through implementation of an Acute Care Urology model. (May 2019) - Kirubarajan, A.; Buckley, R.; Khan, S.; Richard, R.; Stefanova, V.; Chin, A.; Golda, N.
Abstract : Introduction : Renal colic is one of the most common presentations to the emergency department (ED), and often requires complex interdisciplinary collaboration between emergency physicians and urology surgeons. Previous literature has shown that adoption of interdisciplinary rapid referral clinics can improve both timeliness of care and patient outcomes. However, these Acute Care Surgery models have not yet been commonly adopted for urology care in the ED.Methods : In July 2016, we adopted the intervention of an Acute Care Urology (ACU) model through the creation of a rapid referral clinic dedicated to ED patient referrals, the addition of an ACU surgeon, and enhanced use of daytime OR blocks. We conducted a manual chart review of 579 patients presenting to the ED with a complaint of renal colic. Patient data was collected in two separate time periods to analyze trends before implementation of the ACU model (pre-intervention, September - November 2015), to examine the model's impact (post-intervention, September - November 2016). Secondary methods of evaluation included a survey of 20 ED physicians to capture subjective feedback through Likert scale data.Results : Of the evaluated 579 patients with a complaint of renal colic, 194 patients were discharged from ED with an diagnosis of obstructing kidney stone and were referred to urology for outpatient care. The ED-to-clinic time was significantly lower for those in the ACU model (p <0.001). The mean time to clinic was 15.76 days (SD = 15.47, range 1-93) pre-intervention versus 4.17 days (SD = 2.33, range = 1-12) post-intervention. Furthermore, the ACU clinic allowed significantly more patients to be referred for outpatient care (p = 0.0004). There was also higher likelihood that patients would successfully obtain an appointment following referral (p = 0.0055). Decreasing trends were shown in mean ED wait time, in addition to time from assessment to procedure. Results of the qualitative survey were overwhelmingly positive. All 20 surveyed ED physicians were more confident that outpatients would be seen in a timely manner (85% strongly agree, 15% agree). Qualitative feedback included the belief that follow-up is more accessible, that ED physicians are less likely to page the on-call urologist, and that they are able to discharge patients sooner.Conclusion : The ACU model for patients with renal colic may be beneficial in reducing ED-to-clinic time, ensuring proper follow-up after ED diagnosis, and improving patient care within the ED.